2023
DOI: 10.1002/smll.202206966
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Nanospheres with Polycrystalline Ir&Cu and Amorphous Cu2O toward Energy‐Efficient Nitrate Electrolysis to Ammonia

Abstract: Electrochemical reduction reaction of nitrate (NITRR) provides a sustainable route toward the green synthesis of ammonia. Nevertheless, it remains challenging to achieve high‐performance electrocatalysts for NITRR especially at low overpotentials. In this work, hierarchical nanospheres consisting of polycrystalline Iridium&copper (Ir&Cu) and amorphous Cu2O (CuxIryOz NS) have been fabricated. The optimal species Cu0.86Ir0.14Oz delivers excellent catalytic performance with a desirable NH3 yield rate (YR) up to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…[ 146 ] synthesized a RhCu nanocube modified by polyallylamine (denoted as PA‐RhCu), and the nanocube presented a concave and twisted surface, indicating the possible existence of high‐index facet (Figure 6d), and this structure can expose more active sites with low‐coordinated structures unlike well‐crystallized materials with ordered atom arrangement. [ 147–150 ] RhCu exhibited a larger electrochemically active surface area than Rh (72.8 versus 21.6 m 2 g −1 ) according to the CO stripping experiment (Figure 6e). Correspondingly, PA‐RhCu showed far higher NH 3 FE (93.7%) with a small overpotential (Figure 6f), and it is worth mentioning that nitrate reduction was tested under 0.1 m HClO 4 for this material, which is different from the mainstream test in neutral or alkaline solution considering the dissolution of metal in acid environment.…”
Section: Electrochemical Nitrate Reduction To Ammoniamentioning
confidence: 93%
“…[ 146 ] synthesized a RhCu nanocube modified by polyallylamine (denoted as PA‐RhCu), and the nanocube presented a concave and twisted surface, indicating the possible existence of high‐index facet (Figure 6d), and this structure can expose more active sites with low‐coordinated structures unlike well‐crystallized materials with ordered atom arrangement. [ 147–150 ] RhCu exhibited a larger electrochemically active surface area than Rh (72.8 versus 21.6 m 2 g −1 ) according to the CO stripping experiment (Figure 6e). Correspondingly, PA‐RhCu showed far higher NH 3 FE (93.7%) with a small overpotential (Figure 6f), and it is worth mentioning that nitrate reduction was tested under 0.1 m HClO 4 for this material, which is different from the mainstream test in neutral or alkaline solution considering the dissolution of metal in acid environment.…”
Section: Electrochemical Nitrate Reduction To Ammoniamentioning
confidence: 93%
“…[ 144 ] The Ir incorporation was also effective to enhance the nitrate reduction and ammonia selectivity on amorphous copper oxides. [ 141 ] The improved catalytic activity should be attributed to the accelerated electron transfer and enhanced reaction kinetics, while the improvement in selectivity should be contributed by the larger electronegativity of doped Ir sites and correspondingly enhanced the adsorption of reactants, including NO 3 − and H + .…”
Section: Catalysts For E‐no3rrmentioning
confidence: 99%
“…[139,140] The incorporation of other elements is effective to tune the electronic property for various applications. [141][142][143] Xu and coworkers reported that Pd-incorporated Cu 2 O octahedra had an improved ammonia yield of 925.11 μg h −1 mg cat −1 at -1.3 V versus RHE with an FE of 96.56% [143] because of the formation of the Cu-Pd dimers and oxygen vacancies. Du et al reported the Zn-doped CuO nanosheets with a greatly improved ammonia yield.…”
Section: Copper Oxidesmentioning
confidence: 99%
“…Electrocatalytic ammonia synthesis via the nitrate reduction reaction (NITRR) is an eight-electron transfer process involving a series of side products including hydrogen, nitrogen, nitrite, and other compounds, leading to a lower Faraday efficiency of the ammonia synthesis at high current densities. To improve the NITRR, noble metal-based catalysts, such as Pd, Ru, Ir, Au, and Pt, have received special attention due to their high conductivity, low-coordination surface, excellent durability, and appropriate adsorption energy for various reactants. However, the scarcity and high price of precious metal catalysts are limiting factors hindering the industrial application of catalytic NITRR processes.…”
Section: Introductionmentioning
confidence: 99%